219k views
4 votes
Lin decides to solve the equation using the quadratic formula. Here is her work: xxx=−b±b2−4ac−−−−−−−√2a=−(−6)±(−6)2−4(1)(10)−−−−−−−−−−−−−√2(1)=6±36−40−−−−−−√2 Lin knows 36−40 is a negative number and isn't sure what to do next. Show how Lin can write her solution using i.

1 Answer

0 votes

Answer:


x = 3 + i\ or\ x = 3 - i

Explanation:

Given


x = (-(-6) \± √((-6)^2 - 4(1)(10)))/(2*1)

Required

Solve, in terms of i

We have:


x = (-(-6) \± √((-6)^2 - 4(1)(10)))/(2*1)

Solve the expressions in bracket


x = (-(-6) \± √(36 - 40))/(2*1)


x = (-(-6) \± √(-4))/(2)

Express -4 as 4 * -1


x = (-(-6) \± √(-4*1))/(2)

Split


x = (-(-6) \± √(4)*√(-1))/(2)

In complex numbers;


i = \sqrt{-1

So, we have:


x = (-(-6) \± 2*i)/(2)


x = (6 \± 2i)/(2)

Factorize


x = (2(3 \± i))/(2)


x = 3 \± i

Split


x = 3 + i\ or\ x = 3 - i

User Kuntal Shaw
by
4.7k points